Mobility of charge carriers in mineral oil and ester fluids. Issue 6 (8th May 2021) - Xue, Qingjiang; Timoshkin, Igor; Wilson, Mark P.; Given, Martin; MacGregor, Scott J.
Abstract: New, more stringent environmental requirements for electrical insulation liquids have led to the development of novel, more environment‐friendly liquid dielectrics. Ester fluids, introduced several decades ago, provide a viable alternative to traditional mineral insulating liquids. In order to expand the practical applications of these novel dielectric fluids, their dielectric and electrical parameters should be established. One of the critical parameters that affects and governs the development of pre‐breakdown processes in insulating liquids is the mobility of charge carriers. In the present paper, the mobility of charge carriers in commercially available synthetic and natural insulating ester fluids and in a mineral insulating oil were obtained using two methods, the time of flight and the space charge saturation current methods. The mobility was obtained for a wide range of electrical field magnitudes. It was found that the mobility of charge carriers is greater in the mineral oil than in both, the natural and synthetic, ester fluids. It was also established that the mobility is higher for higher applied electric field. The results of this work will help in characterizing liquid dielectrics and in optimizing high‐voltage systems in which liquid dielectrics, including natural and synthetic ester fluids, are used.